2020
DOI: 10.14236/ewic/hci20dc.5
|View full text |Cite
|
Sign up to set email alerts
|

“Why Sideload?” User Behaviours, Interactions and Accessibility Issues Around Mobile App Installation

Abstract: With the increase of smartphone ownership year by year, the accessibility of mobile application increases too. Application sideloading is a behaviour identified as the act of installing applications through unofficial means. Moreover, sideloading as a study is insufficiently researched in relation to its occurrence in smartphone usage. This position paper describes sideloading behaviour in context to accessibility, interaction, security, problematic smartphone uses and its occurrences in other devices. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As more devices become vintage and obsolete, a larger and more comprehensive comparative study could be conducted to assess and 'rank' changes in performance and usefulness across multiple systems. Furthermore, a similar study methodology could potentially be ap-plied to other smartphone and tablet devices such as Android devices with "download via another device" replaced by the "sideloading" of apps [11]. This device compared to a similar era Android device has much less developer support and has a higher prob-ability of becoming e-waste sooner as the limitations on usage become more prevalent.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…As more devices become vintage and obsolete, a larger and more comprehensive comparative study could be conducted to assess and 'rank' changes in performance and usefulness across multiple systems. Furthermore, a similar study methodology could potentially be ap-plied to other smartphone and tablet devices such as Android devices with "download via another device" replaced by the "sideloading" of apps [11]. This device compared to a similar era Android device has much less developer support and has a higher prob-ability of becoming e-waste sooner as the limitations on usage become more prevalent.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…As more devices become vintage and obsolete, a larger and more comprehensive comparative study could be conducted to assess and 'rank' changes in performance and usefulness across multiple systems. Furthermore, a similar study methodology could potentially be applied to other smartphone and tablet devices such as Android devices with "download via another device" replaced by the "sideloading" of apps [11]. This device compared to a similar era Android device has much less developer support and has a higher probability of becoming e-waste sooner as the limitations on usage become more prevalent.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…A preliminary scoping study of the literature categorized sideloading drivers and motivations as broadly: ideological, behavioural and practical (Goodwin, 2020). However, there have been no previously published studies in the academic literature that have reported empirical findings for sideloading drivers and motivations.…”
Section: Related Work and Contextmentioning
confidence: 99%